(untitled) (Jurnal Manajemen dan Kewirausahaan, 2007)
The main objective of the study is to examine the impact of ownership structure%2C leverage%2C external factor%2C internal factor on the value of the firms in Jakarta Stock Exchange. It is argued that unlike the agency problem advanced stock market%2C the agency problem in the Jakarta Stock Exchange is the divergence of interest between the minority holders and majority holders. This is because the Jakarta Stock Exchange is characterized%2C among other things%2C by the domination of large shareholders. It is hypotheses that :(1) there are the impact ownership structure %2C external factor%2C internal factor%2C on leverage%2C (2) there are the impact of ownership structure %2C external factor%2C internal factor%2C leverage on value of the firm . This study is to examine Agency Theory%2C Jensen and Meckling (1976)%2C Pecking Order Theory%2C Myers (1984)%2C Trade Off Model and Signaling Theory (1979). Population in this study are public company listed in Jakarta Stock Exchange during 2000 – 2004. As much as 134 firms listed in Jakarta Stock Exchange were taken as a sample using a purposive sampling method.The data were then analyzed by the structural equation modeling ( SEM) analysis%2C using the AMOS Program version 4.01.The results of this study show that (1) there are the impact of ownership structure %2C external factor%2C internal factor on leverage%2C(2)there are the impact of ownership structure%2C external factor%2C internal factor%2C leverage%2C on valueof the firm . The result of the study is not support the Agency Theory%2C Jensen and Meckling (1976)%2C but the result of the study is support Pecking Order Theory%2C Myers (1984)%2C Trade off model and Signaling Theory%2C Battacharya (1979). Abstract in Bahasa Indonesia : Tujuan utama dari studi ini adalah untuk menguji pengaruh struktur kepemilikan%2C leverage%2C faktor ekstern%2C dan faktor intern terhadap nilai perusahaan di Bursa Efek Jakarta. Tidak seperti pada permasalahan keagenan di pasar modal yang sudah maju%2C problem keagenan di Bursa Efek Jakarta adalah terjadinya perbedaan kepentingan antara pemilik minoritas dengan pemilik mayoritas. Hipotesis dalam penelitian ini adalah : (1) struktur kepemilikan%2C faktor ekstern%2C dan faktor intern berpengaruh signifikan terhadap leverage%2C (2) struktur kepemilikan%2C faktor ekstern%2C faktor intern dan leverage berpengaruh signifikan terhadap nilai perusahaan. Studi ini ingin menguji teori keagenan%2C Jensen dan Meckling (1976)%2C Pecking Order Theory%2C Myers (1984)%2C Trade off model dan Signaling Theory%2C Bhattacharya (1979). Populasi dalam studi ini adalah perusahaan publik yang terdaftar di Bursa Efek Jakarta. Sebanyak 134 perusahaan diambil sebagai sample dengan enggunakan purposive sampling. Data dianalisis dengan mengunakan Structural Equation Modelling. Hasil studi ini menunjukkan bahwa struktur kepemilikan%2C faktor intern dan faktor ekstern berpengaruh signifikan terhadap leverage. Struktur kepemilikan%2C faktor ekstern%2C faktor intern%2Cdan leverage berpengaruh signifikan terhadap nilai perusahaan.Hasil studi ini tidak mendukung teori keagenan%2C Jensen dan Meckling (1976) tetapi hasil studi ini mendukung Pecking Order Theory%2C Myers (1984)%2C Trade off model dan Signaling theory%2C Bhattacarya (1979). TobinsÂ’Q%2C leverage%2C ownership structure.